Patterns of urban public space utilisation in an African city and rapid urbanisation : social and economic networks and their influence on public space on Robert Sobukwe Street, Sunnyside - Toffah, Tariq (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2024.